2005
DOI: 10.1007/s00705-005-0538-5
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of immunoblot test stripes from a Rubella virus-like particles dye crystal complex as antigen

Abstract: Stably transfected Chinese hamster ovary (CHO24S) cells were the source for Rubella virus-like particles (RVLP) containing all structural proteins (E1, E2, C and their dimers). RVLP are secreted from the CHO24S cells into the medium and the time-point for collecting the medium with the highest yield of >100 kDa proteins (with 17 mg protein from 10 ml cell culture supernatant) was after 2 days of incubation. Different methods for RVLP isolation from the cell culture supernatants were assessed by SDS-PAGE and We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…In contrast, rubella-like particles or RLPs were shown to be formed by the RUBV virion proteins without detectable RNA (Hobman et al , 1994; Qiu et al , 1994) and have been used to study protein function [e.g. that dimerization of the CP is not necessary for particle formation (Lee et al , 1996)], as prototype inactivated vaccines and for immunological assays (Giessauf et al , 2005; Grangeot-Keros & Enders, 1997; Pustowoit et al , 1996). In this study, we showed for the first time that RUBV replicons could be efficiently packaged into VRPs.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, rubella-like particles or RLPs were shown to be formed by the RUBV virion proteins without detectable RNA (Hobman et al , 1994; Qiu et al , 1994) and have been used to study protein function [e.g. that dimerization of the CP is not necessary for particle formation (Lee et al , 1996)], as prototype inactivated vaccines and for immunological assays (Giessauf et al , 2005; Grangeot-Keros & Enders, 1997; Pustowoit et al , 1996). In this study, we showed for the first time that RUBV replicons could be efficiently packaged into VRPs.…”
Section: Discussionmentioning
confidence: 99%